POLA DAN SENSITIVITAS TERHADAP ANTIBIOTIK BAKTERI PENYEBAB INFEKSi SALURAN KEMIH ANAK DI RSU DR SAIFUL ANWAR, MALANG - Subandiyah, Krisni (Jurnal Kedokteran Brawijaya, 2004)
ABSTRACT Urinary tract infection (UTI) is one of the most common bacterial infections affecting children. Early recognition and prompt treatment of UTIs are important to prevent progression of infections and to avoid late sequeale. The aim of the study was to identify the bacterial agents of urinary tract infections in children and to study sensitivity to antibiotics. Urinary specimens were collected from children suffering from urinary tract infections, who were either inpatients or outpatients between January 1999 and December 2003. Of a total of 563 urine specimens, bacteriuria was found in 276 (49.02%) of patients. Females showed a higher prevalence of infection (51.1%) than  males  (48.9%).  Mean  age  was  63  months,  median age  was  60  months  (range  1  month  to  12  years).  The microorganisms isolated  from  children  included  Escherichia  coli  (48.9%),  Acinetobacter  anitratus  (9.8%),  Klebsiella  pneumoniae  (9.4%), Staphylococcus positive coagulase (5.8%), Proteus mirabilis (4.7%), others (21.4%). Escherichia coli was sensitive to nitrofurantoin (74.8%),  nalidixic  acid  (69.6%),  cefotaksim  (48.9%),  Amoxcillin  clavulanat  acid  (37.8%),  fosfomicin  (35.6%),  gentamicin  (34.1%), ceftriaxone (31.8%), amikacin (19.2%), cotrimoxazole (15.6%), ciprofloxacin (11.1%), cefuroxim (3.7%), netilmicin (8.9%), amoxcilin (2.9%),  chloramphenicol  (2.2%),  ampicilin  (2.2%).  Resistant  to  ampicillin  dan  chloramphenicol  97.8%.  Acinetobacter  anitratus sensitive to nalidixic acid (62.96%), Amoxcillin clavulanat acid (48.15%), gentamicin (40.74%), co-trimoxazole (33.33%), nitrofurantoin (25.93%), amoxcilin (25.93%), amikacin (11.11%), netilmycine (11.11%), ampicillin (7.40%), ciprofloxacin (7.40%), cefotaxim (7.4%), ceftriaxon (7.4%), cefuroxim (3.7%).